Human placental renin–angiotensin system in normotensive and pre-eclamptic pregnancies at high altitude and after acute hypoxia–reoxygenation insult - Kurlak, L.O.; Mistry, Hiten D.; Cindrova-Davies, Tereza; Burton, Graham; Broughton Pipkin, Fiona (Wiley, 2016)
A functioning placental renin–angiotensin system (RAS) appears necessary for uncomplicated pregnancy and is present during placentation, which occurs under low oxygen tensions. Placental RAS is increased in pre-eclampsia (PE), characterised by placental dysfunction and elevated oxidative stress. We investigated the effect of high altitude hypoxia on the RAS and hypoxia-inducible factors (HIFs) by measuring mRNA and protein expression in term placentae from normotensive (NT) and PE women who delivered at sea level or above 3100 m, using an explant model of hypoxia–reoxygenation to assess the impact of acute oxidative stress on the RAS and HIFs. Protein levels of prorenin (P = 0.049), prorenin receptor (PRR; P = 0.0004), and angiotensin type 1 receptor (AT1R, P = 0.006) and type 2 receptor (AT2R, P = 0.002) were all significantly higher in placentae from NT women at altitude, despite mRNA expression being unaffected. However, mRNA expression of all RAS components was significantly lower in PE at altitude than at sea level, yet PRR, angiotensinogen (AGT) and AT1R proteins were all increased. The increase in transcript and protein expression of all the HIFs and NADPH oxidase 4 seen in PE compared to NT at sea level was blunted at high altitude. Experimentally induced oxidative stress stimulated AGT mRNA (P = 0.04) and protein (P = 0.025). AT1R (r = 0.77, P < 0.001) and AT2R (r = 0.81, P < 0.001) mRNA both significantly correlated with HIF-1β, whilst AT2R also correlated with HIF-1α (r = 0.512, P < 0.013). Our observations suggest that the placental RAS is responsive to changes in tissue oxygenation: this could be important in the interplay between reactive oxygen species as cell-signalling molecules for angiogenesis and hence placental development and function.